Professor Alberto Guzmán Barrón (1904 - 1988). Semblance - Delgado Butrón, Leonidas (1996)
Institutions are perennizan in time, while humans face an inexorable cyclical; this fact makes today are occupying these pages once a semblance of distinguished and exemplary Teacher of the Faculty of Medicine of San Fernando: Dr. Alberto Guzmán Barrón; written sketch recognition disciple, colleague respect and affection of the friend, who remembers his make parsimonious, their passengers and timely attacks 'deafness', her slow and quiet, serenity always showing even during tough times.